2018
DOI: 10.1002/jcp.27946
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA GACAT3 promotes glioma progression by sponging miR‐135a

Abstract: The long noncoding RNA (lncRNA) gastric cancer associated transcript 3 (GACAT3) has been reported to play important roles in human tumorigenesis. However, its expression pattern, functions, and underlying mechanism in glioma remain unclear. In the present study, we showed that GACAT3 is upregulated in glioma tissues and cell lines. Through online databases, luciferase reporter assays and RNA immunoprecipitation (RIP) assays, we determined that GACAT3 acts as a competing endogenous RNA (ceRNA) for microRNA (miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
(27 reference statements)
2
24
0
Order By: Relevance
“…Therefore, our data identified LINC00526 as a potential prognostic biomarker for glioma and suggested that ectopic expression of LINC00526 may be a potential therapeutic strategy for glioma. LncRNAs GAS5, NEAT1, GACAT3, CASC9, HMMR‐AS1, LINC00152, HOTAIRM1, AC003092.1, HOXD‐AS1, OIP5‐AS1, DANCR and so on have been reported to play oncogenic or tumour suppressive roles in glioma . Our study further proved the critical roles of lncRNAs in glioma and provided another candidate lncRNA for glioma prognosis and therapy.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, our data identified LINC00526 as a potential prognostic biomarker for glioma and suggested that ectopic expression of LINC00526 may be a potential therapeutic strategy for glioma. LncRNAs GAS5, NEAT1, GACAT3, CASC9, HMMR‐AS1, LINC00152, HOTAIRM1, AC003092.1, HOXD‐AS1, OIP5‐AS1, DANCR and so on have been reported to play oncogenic or tumour suppressive roles in glioma . Our study further proved the critical roles of lncRNAs in glioma and provided another candidate lncRNA for glioma prognosis and therapy.…”
Section: Discussionsupporting
confidence: 63%
“…Overexpression of GACAT3 in lung cancer cells promoted cell proliferation and migration (13), and it enhanced their sensitivity to radiotherapy. GACAT3 was recently demonstrated to promote progression of colorectal cancer (14), breast cancer (15), and glioma (16,17). However, the role of GACAT3 in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis revealed two complementary sites of miR-135a in UCA1, and a luciferase activity assay confirmed that miR-135a was a target of UCA1 and was decreased by UCA1 46 . Similarly, GACAT3 decreased miR-135a expression by acting as a ceRNA 47 , similar to FOXD3-AS1 and MBNL1-AS1 48 , 50 . MiR-135a is also sponged by SNHG16, and this process is promoted by activation of the JAK2/STAT3 pathway 51 .…”
Section: Mechanisms Of Mir-135a Dysregulation In Cancermentioning
confidence: 82%
“…Other studies have shown that miR-135a is also regulated by interactions with long non-coding RNAs (lncRNAs), such as urothelial carcinoma associated 1 (UCA1) 46 , gastric cancer associated transcript 3 (GACAT3) 47 , FOXD3 antisense RNA 1 (FOXD3-AS1) 48 , differentiation antagonizing nonprotein coding RNA (DANCR) 49 , muscleblind-like 1 antisense RNA 1 (MBNL1-AS1) 50 , and the small nucleolar RNA host gene 16 (SNHG16) 51 . These lncRNAs act as competing endogenous RNAs (ceRNAs) by binding to miRNAs via miRNA response elements 52 .…”
Section: Mechanisms Of Mir-135a Dysregulation In Cancermentioning
confidence: 99%